PENGATURAN HUKUM PERSAINGAN USAHA ATAS JASA KEUANGAN DIGITAL DI INDONESIA - Muhammad Arif Fahmi; M. Afif Hasbullah; Ahmad Munir (Universitas Islam Darul Ulum, 2022)
The revolution from industry 4.0 has created a new finding in the financial sector, namely digital finance. The unclear legal rules governing business competition in the digital financial services industry can lead to cartel actions in conducting business competition. The method used in writing this article is normative legal research on the phenomenon of the development of the digital financial era in Indonesia. This study aims to analyze the legal regulation of business competition for digital financial services and fair business competition in the digital financial services industry. The regulation of digital financial services in Indonesia is regulated in Bank Indonesia Regulation Number 19/12/PBI/2017 concerning the Application of Financial Technology, and is also regulated in the Financial Services Authority Regulation No. 13 /POJK.02/2018 regarding digital financial innovation, it also includes consumer protection for digital financial service users. However, to guarantee legal certainty for the community or consumers, it must be regulated in the form of a law.